Ten Broad Spectrum Resistances to Downy Mildew Physically Mapped on the Sunflower Genome - Pecrix, Yann; Penouilh-Suzette, Charlotte; Muños, Stéphane; Vear, Felicity; Godiard, Laurence (Frontiers in Plant Science, 2018)
Resistance to downy mildew (Plasmopara halstedii) in sunflower (Helianthus annuus L.) is conferred by major resistance genes, denoted Pl. Twenty-two Pl genes have been identified and genetically mapped so far. However, over the past 50 years, wide-scale presence of only a few of them in sunflower crop led to the appearance of new, more virulent pathotypes (races) so it is important for sunflower varieties to carry as wide a range of resistance genes as possible. We analysed phenotypically 12 novel resistant sources discovered in breeding pools derived from two wild Helianthus species and in eight wild Helianthus annuus ecotypes. All were effective against at least 16 downy mildew pathotypes. We mapped their resistance genes on the sunflower reference genome of 3,600Mb, in intervals that varied from 75Kb to 32Mb using an AXIOM® genotyping array of 49,449 SNP. Ten probably new genes were identified according to resistance spectrum, map position, hypersensitive response to the transient expression of a P. halstedii RXLR effector, or the ecotype / species from which they originated. The resistance source HAS6 was found to carry the first downy mildew resistance gene mapped on chromosome 11, whereas the other resistances were positioned on chromosomes 1, 2, 4 and 13 carrying already published Pl genes that we also mapped physically on the same reference genome. The new genes were designated Pl23-Pl32 according to the current nomenclature. However, since sunflower downy mildew resistance genes have not yet been sequenced, rules for designation are discussed. This is the first large scale physical mapping of both ten new and ten already reported downy mildew resistance genes in sunflower.